Surgical Treatment of Esophagoenteroanastomosis Leakage after Total Gastrectomy - I. N. Peregorodiev; I. A. Zaderenko; K. A. Batyrov; S. N. Nered (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
Aim: to present the difficulties of the choice of surgical tactics in case of esophagoenteroanastomosis suture failure after gastrectomy.Key points. In patient K., 55 years old, after a planned surgical intervention involving gastrectomy for stomach cancer, leakage of the esophagoenteroanastomosis sutures was noted. An attempt to re-form the esophageal-intestinal anastomosis did not lead to success, despite the early stages of relaparotomy, therefore, in order to relieve purulent complications, it was decided to take the path of “disconnecting” the esophagus, for which the cervical esophagus was transected and brought out in the form of two stomas, and the distal end of the esophagus was sutured tightly. Adequate drainage of the esophageal stump area and disconnection of the esophagus at the cervical level made it possible to avoid purulent complications in the abdominal cavity. The reconstructive stage was performed after 6 months in the amount of a colonic insert between the distal esophagus and the jejunum and plastic surgery of the esophagus using a skin insert in the neck.Conclusion. The chosen treatment tactics was determined by the impossibility of conservative treatment of the suture failure of the esophageal-intestinal anastomosis due to ischemic disorders and necrosis of the small intestine anastomosed with the esophagus. Disconnection of the esophagus after repeated suture failure of the esophageal-intestinal anastomosis seemed to be the only chance to stop the flow of esophageal contents into the abdominal cavity and thereby eliminate the source of purulent complications. The esophagoplasty option used turned out to be the safest and allowed to save the patient’s life.